Study on Factors Affecting Separation of Xylose From Glucose By Nanofiltration Using Composite Membrane Developed From Triethanolamine (Teoa) And Trimesoyl Chloride (TMC) - Mah, Kah Hong; Wan Mohd Hafizuddin, Wan Yussof; Mazrul Nizam, Abu Seman; Nurul Ain , Jalanni; N., Zainol (2014)
Xylose is an abundant raw material coexists with other sugars that can be converted into xylitol. Separation of monosaccharides from each other is carried out commercially by chromatographic method. Nanofiltration may offer alternative to the current in use chromatographic method. This work aims to study the influence of pressure, total sugar concentration and xylose/glucose ratio on separation process using two-level factorial analysis. Membrane was prepared by conventional interfacial polymerization of triethanolamine (TEOA) and tri-mesoyl chloride (TMC) on polyethersulfone (PES) porous membrane. The experiment was performed using Amicon Milipore stirred cell with constant stirring speed at 300 rpm and at ambient temperature. The glucose and xylose concentration was quantified using high performance liquid chromatography (HPLC). In this study, it was found that the xylose/glucose ratio has affected the nanofiltration the most, at 63.56 %, followed by total sugar concentration at 19.52 %, and pressure contributed the least at 0.033 %. An interaction between factor total sugar concentration and composition of xylose to glucose were also found to contribute 16.10 % on nanofiltration. The coefficient of determination (R2) from analysis of variance (ANOVA) study was 0.9921. Overall, in this present work it can be concluded that nanofiltration has high potential to replace chromatographic method in xylose separation.